The Sculpted Recumbent Effigy of Marie Gaudin at the Church of Saint Denis in Amboise: History and Artistic Context - Baydova, Anna (Actual Problems of Theory and History of Art, 2017)
The sculpture from the 16th century of a naked woman on her deathbed, preserved at the church of Saint Denis in Amboise, is usually referred to in bibliography as “the drowned woman” and was attributedby local tradition to the Italian painter Primaticcio. This attribution has been challenged for a long time, but the circumstances surrounding the commission remained unknown. The history of this work, moved several times, was revealed by Alfred Gabeau at the end of the 19th century; it can now be completed and clarified by the study of documents and iconographic sources preserved in archives and libraries of France.The purpose of this article is to identify and to list the historical sources concerning this work, to take stock of its history and to place this funerary monument in its artistic context in order to better understand the circumstances of this important commission. The study confirms the identification of the recumbent effigy as a statue of Marie Gaudin, the widow of the rich financier Philibert Babou from Tours. Taking as an example the royal tombs at the basilica of Saint Denis, this commission demonstrates the practices and artistic strategies of the refined aristocracy of the Renaissance.
Keywords: Renaissance; Touraine; Amboise; Church of Saint Denis; sculpture; Marie Gaudin; recumbent effigy; archives